Calibrated, Multiband Radiometric Measurements of the Optical Radiation from Lightning - Quick, Mason G. (The University of Arizona., 2014)
Calibrated, multiband radiometric measurements of the optical radiation emitted by rocket-triggered lightning (RTL) have been made in the ultraviolet (UV, 200-360 nm), the visible and near infrared (VNIR, 400-1000 nm), and the long wave infrared (LWIR, 8-12 µm) spectral bands. Measurements were recorded from a distance of 198 m at the University of Florida International Center for Lightning Research and Testing (ICLRT) during the summers of 2011 and 2012. The ICLRT provided time-correlated measurements of the current at the base of the RTL channels. Following the onset of a return stroke, the dominant mechanism for the initial rise of the UV and VNIR waveforms was the geometrical growth of the channel in the field-of-view of the sensors. The UV emissions peaked about 0.7 µs after the current peak, with a peak spectral power emitted by the source per unit length of channel of 10 ± 7 kW/(nm-m) in the UV. The VNIR emissions peaked 0.9 µs after the current peak, with a spectral power of at 7 ± 4 kW/(nm-m). The LWIR emissions peaked 30-50 µs after the current peak, and the mean peak spectral power was 940 ± 380 mW/(nm-m), a value that is about 4 orders of magnitude lower than the other spectral band emissions. In some returns strokes the LWIR peak coincides with a secondary maximum in the VNIR band that occurs during a steady decrease in channel current. Examples of the optical waveforms in each spectral band are shown as a function of time and are discussed in the context of the current measured at the channel base. Source power estimates in the VNIR band have a mean and standard deviation of 2.5 ± 2.2 MW/m and are in excellent agreement with similar estimates of the emission from natural subsequent strokes that remain in a pre-existing channel which have a mean and standard deviation of 2.3 ± 3.4 MW/m. The peak optical power emitted by RTL in the UV and VNIR bands are observed to be proportional to the square of the peak current at the channel base. The same trend was found for natural lightning using peak currents estimates provided by the National Lightning Detection Network. Ratios of the optical power to the electromagnetic power emitted at the time of peak current suggest the radiative efficiency in the VNIR band is a few percent during the early onset of a return stroke. The majority of return strokes in RTL are found to emit most of their optical energy during the initial impulse phase.